The Role of Indigenous Peoples, Social Workers, and the Syar’iyah Court in Diversion of Children Perpetrators of Jinayah - Zulfia Hanum Alfi Syahr; Tumbur Palti D. Hutapea; Umma Farida; Dian Hafit Syaifullah; Buyamin (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
The juvenile justice system as a legal efforcement to guarantee the rights of children who conflict with the law. The mechanism for the criminal justice system against children is carried out through diversion involving judicial officials. However, problems arise in enforcing the criminal justice system for children engaged in Jinayah cases. It is because the Jinayah case must obey the qanun implemented in Aceh. The punishment given to the perpetrators of Jinayah can be in the form of flogging or imprisonment. For a child, that punishment can be traumatic for the child’s mental health. Therefore, this research will examine various efforts to minimize the impact of this punishment on the psychological development of children who become perpetrators of Jinayah. The problem of this study is how a child can maintain his psychological health after becoming a perpetrator of Jinayah. This research is essential to protect children’s psychological development as perpetrators of Jinayah. The purpose of this study is to find various efforts to maintain the mental development of children as perpetrators of Jinayah. Thus, the research method used to answer these problems is qualitative with a normative approach and literature study. The normative research will analyze various legal regulations regarding criminal and Jinayah acts. Then, it will support a literature study to gain a comprehensive and depth understanding of the topic of study. The results are that children as perpetrators of Jinayah have a risk of psychological trauma, and juvenile criminal law needs to be strengthened. Strengthening this law can be in the form of harmonizing the diversion of children with the Jinayah law. The cooperation of various parties, namely, law enforcement officials, social workers, and indigenous peoples, can minimize the risk of child psychological trauma.